Methods of Training Teachers to use Electronic Information Education Resources and Their Flexibility (Eurasian Scientific Herald, 2022)
The article notes that it is convenient to use the hierarchical structure of information created, represented, visualized, processed, stored, transmitted and managed using information and telecommunication technologies.